2012
DOI: 10.1063/1.4734489
|View full text |Cite
|
Sign up to set email alerts
|

CHEMO-hydrodynamic coupling between forced advection in porous media and self-sustained chemical waves

Abstract: Autocatalytic reaction fronts between two reacting species in the absence of fluid flow, propagate as solitary waves. The coupling between autocatalytic reaction front and forced simple hydrodynamic flows leads to stationary fronts whose velocity and shape depend on the underlying flow field. We address the issue of the chemico-hydrodynamic coupling between forced advection in porous media and self-sustained chemical waves. Towards that purpose, we perform experiments over a wide range of flow velocities with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 49 publications
2
7
0
1
Order By: Relevance
“…Such propagation in simple flows has been addressed recently [7,9]. In more complex situations from the point of view of either the chemistry [10,11] or the flow field [8,[12][13][14], it has been reported that when the flow is opposing the chemical front, frozen, i.e., static, fronts can be observed not only for a particular flow intensity, but also over a wide range of flow intensity values. Those frozen states have been observed experimentally but not fully understood.…”
mentioning
confidence: 99%
“…Such propagation in simple flows has been addressed recently [7,9]. In more complex situations from the point of view of either the chemistry [10,11] or the flow field [8,[12][13][14], it has been reported that when the flow is opposing the chemical front, frozen, i.e., static, fronts can be observed not only for a particular flow intensity, but also over a wide range of flow intensity values. Those frozen states have been observed experimentally but not fully understood.…”
mentioning
confidence: 99%
“…Above a critical temperature, the front remains stable and thus planar. In a combination of experiments and Lattice-Boltzmann based simulations, Atis et al 51 complement the foregoing works by two new elements. First, they study the interaction of autocatalytic fronts with porous media.…”
Section: Convection Around Self-organized Reaction Frontsmentioning
confidence: 88%
“…For downstream fronts, the separation between the two branches becomes thinner and thinner as u increases and can lead to a pinch-off, followed by a detachment as observed in [17].…”
Section: Two Types Of Frozen Front In Uniform Flow Past a Solid Diskmentioning
confidence: 99%
“…These fronts are analogous to flames in combustion [4] and autocatalytic reactions are a kind of "cold combustion model" especially in the thin flame limit. In contrast to flame propagation in combustion [4], where it has been analyzed thoroughly theoretically and experimentally, the effect of fluid flow (laminar or turbulent) on reaction fronts has not been explored in detail until recently [5][6][7][8][9][10][11][12][13][14][15][16][17][18]. In the presence of an hydrodynamic flow, it has already been observed and understood that such fronts while propagating at a new constant velocity, adapt their shape in order to achieve a balance between reaction diffusion and flow advection.…”
Section: Introductionmentioning
confidence: 99%